Using different approaches to organizing distance learning during the COVID-19 pandemic: opportunities and disadvantages - Danchikov, Evgeniy Aleksandrovich; Prodanova, Natalia Alekseevna; Kovalenko, Yulia Nikolaevna; Bondarenko, Tatiana Grigorievna (Linguistics and Culture Review, 2021)
In recent years, distance learning has become widespread in both secondary and higher educational institutions around the world. However, the pace of the spread of remote technologies has significantly increased with the introduction of physical distancing and quarantine against the background of the development of the COVID-19 pandemic, since most educational institutions in various countries of the world were closed to hold the spread of the virus. Many educational institutions were not fully ready for the mass introduction of distance learning, and if in developed countries schools and universities had the opportunity to use developments in the educational process of various programs and technologies for conducting online learning, then in countries and regions where there were serious problems with the implementation of distance learning, attempts were made to use the possibilities of social networks and messengers for organizing the educational process. However, since these resources were not fully intended for the implementation of full-fledged pedagogical activities, their use in the educational process, along with the advantages, had several disadvantages.